Comment la gestion des compétences permet-elle de garantir l'employabilité de l'individu? - Akkacha, Hakima; Daoudi, Salah; Khiat, Assya (جامعة حسيبة بن بوعلي الشلف - مخبر تنمية تنافسية المؤسسات الصغيرة والمتوسطة الجزائرية في الصناعات المحلية البديلة, 2019)
The concept of employability takes measurements and quite varied contours in the literature, which certainly implies the development of skills and adaptation to changes in the employees' job. Despite the large number of work on skills and employability, by cons there is little work to understand how to clarify the relationship between these two concepts of HRM. The purpose of our article is to define the answers to the question: how does it allow management skills to ensure the employability of the individual? We offer in this article a conceptual and exploratory approach at the pharmaceutical distributor company in the first part we will present a state of the art on the concepts of individual competence and employability, and their relationships in the second part, we discuss the elements that guarantees the employability of the individual.
Keywords: الإدارة المهنية -- إدارة الموارد البشرية -- التدريب -- الكفاءة المهنية -- التوظيف